Composite gas cylinders – Probabilistic analysis of minimum load cycle requirements. (16th March 2017) - Mair, G.W.; Becker, B.; Duffner, E.; Saul, H.; Schoppa, A.
Abstract: Gas cylinders made of composite materials receive growing popularity in light-weight applications. Current standards are mostly based on safety determination relying on minimum amounts of endured load cycles and a minimum burst pressure of a small number of specimens. This paper investigates the possibilities of a probabilistic strength assessment for safety improvements as well as cost and weight savings. The probabilistic assessment is based on destructive testing of small sized samples. The influence of sample size on uncertainty of the assessment is analysed. Furthermore, methods for the assessment of in-service ageing (degradation) are discussed and displayed in performance charts. Highlights: Production scatter needs to get part of safety assessment of composite cylinders. In case of high scatter unsafe composite cylinders may currently get approved. Strength degradation during service is mainly driven by increase of scatters. The shown performance charts enables simple probabilistic safety surveillance. Probabilistic safety assessment enables optimization beyond current approval limit.